SEL FEEDER DAN CONDITIONED MEDIUM UNTUK KULTUR SEL PUNCA EMBRIONIK MENCIT SEBAGAI MODEL UNTUK PROPAGASI SEL PUNCA EMBRIONIK - Naroeni, Aroem (Indonesian Journal of Biotechnology and Biodiversity, 2017)
AbstractStem cell is very promising for regenerative medicine. Unfortunately, the sources of stem cells are limited. Umbilical cord, bonne marrow are now the most used as stem cell source. Many techniques are now being developed to isolate, propagate and differentiate stem cells. The development of induced-pluripotent stem cells that reprogram adult cells to stem cells are being developed as well. In this research we have developed stem cell culture for the propagation of stem cells by using feeder cells and conditioned medium. Stem cells were isolated from mice embryonicÂ 13 days after copulation. We obtained bulks of stem cells surrounded with mouse fibroblast cells. Stem cells require this mouse fibroblast cells as a feeder and conditioned medium, Medium that have been added with supernatant of 3 days cell culture. Keywords : stem cell, conditioned medium, induced-pluripotent stem cellÂ AbstrakSel punca sangat menjanjikan dalam bidang kedokteran regeneratif karena dapat menyembuhkan berbagai penyakit karena kerusakan jaringan. Meskipun begitu, sumber sel punca yang dapat digunakan untuk keperluan tersebut sangat terbatas. Sel darah pusat dan sumsum tulang belakang saat iniadalah merupakan sumber sel punca yang paling banyak digunakan. Beberapa macam teknik sedang dikembangkan untuk mengisolasi, propagasi dan differensiasi sel punca. Perkembangan induced-pluripotent stem cell (iPS) untuk propagasi sel punca juga sedang dikembangkan. Pada penelitian ini, kami mengembangkan kultur sel untuk propagasi sel punca dengan menggunakan sel feeders dan conditioned medium. Sel punca diisolasi dari embrio mencit 13 hari setelah kopulasi. Setelah dikultur dalam media tersebut maka diperoleh sekelompok sel punca yang dikelilingi oleh sel fibroblas. Sel punca dapat dikembangkan dan dipertahankan sifat kepuncaannya dengan menggunakan sel fibroblas sebagai sel feeder dan penambahan conditioned medium pada media kulturnya.Â Kata kunci : sel punca, conditioned medium, induced-pluripotent stem cell